Penggunaan Kata Kaeru Sebagai Homonim Dalam Anime One Piece Karya Eiichiro Oda - Wardatul Jannah Putri; Meira Anggia Putri (Universitas Negeri Padang, 2025)
A homonym is a word that has the same pronunciation but can have multiple meanings depending on the context. Research on the use of homonyms in modern media, particularly in anime, is important to avoid misinterpretation of meaning. The significance of this study arises from the fact that the grammatical aspects of the Japanese language, including homonyms, differ greatly from those of the Indonesian language, which classifies such aspects lexically. This study aims to describe the use of the homonym kaeru in the anime One Piece by Eiichiro Oda, employing Pateda’s (2010) theory of contextual meaning. The study uses a qualitative approach with a descriptive method. The data in this research consist of dialogue sentences containing the homonym kaeru found in the novel Yuube no Kare, Ashita no Pan by Izumi Kizara. The results show that there are 54 dialogue sentences demonstrating the use of the homonym kaeru. The word kaeru is used as the name of an amphibian animal that can jump and live in two habitats (16 data), as an expression for leaving a place to return home or to one’s place of origin (18 data), to indicate changing something either physically or conceptually (5 data), to express the financial ability to buy something or in the context of discussing purchasing power (3 data), and in the context of exchanging or replacing something with an equivalent (1 data). No data were found for the use of kaeru referring to the ability to raise animals or to someone or something replacing another’s role or function. It is also used in the context of exchanging one object for another (5 data), referring to someone or something returning to its origin in a spiritual or philosophical sense (4 data), describing a physical object returning to its owner or original condition (1 data), and explaining the process of a living being hatching from an egg after an incubation period (1 data).